2019
DOI: 10.3390/su11020445
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Changes in Evapotranspiration from an Overexploited Water Resources Basin in Arid Northern China and Their Implications for Ecosystem Management

Abstract: Evapotranspiration (ET), including evaporation from soil and water surfaces and transpiration from vegetation, influences water distribution in the soil-plant-atmosphere continuum, especially in arid areas where water is a key limiting factor. Therefore, understanding the spatiotemporal dynamics of ET, including its two components of soil evaporation (Es) and vegetation transpiration (Ec), can be useful for water resource management and ecological restoration in arid regions. Based on ET data from 2002 to 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…During the growing season, the ET d distribution in the Shiyang River Basin showed a unimodal variation, with the maximum value occurring in mid-July. The same conclusion was reported by Liu et al [29] using the MOD16 ET product, who suggested that the distribution trend of ET d was related to changes in irrigation water, temperature, precipitation, and vegetation within the Shiyang River Basin. Spatially, ET in the study area decreased from the southwest to northeast.…”
Section: Analysis Of the Et D With Different Lulc Typessupporting
confidence: 85%
See 1 more Smart Citation
“…During the growing season, the ET d distribution in the Shiyang River Basin showed a unimodal variation, with the maximum value occurring in mid-July. The same conclusion was reported by Liu et al [29] using the MOD16 ET product, who suggested that the distribution trend of ET d was related to changes in irrigation water, temperature, precipitation, and vegetation within the Shiyang River Basin. Spatially, ET in the study area decreased from the southwest to northeast.…”
Section: Analysis Of the Et D With Different Lulc Typessupporting
confidence: 85%
“…However, relatively few studies have spatially quantified the actual ET in this region. Liu et al [29] and Tian et al [30] assessed the distribution characteristics and dynamics of actual ET in the Shiyang River Basin using MOD16 ET products. However, it is important to note that the MOD16 ET products excluded the ET in barren/desert areas from the model calculations and set the ET value to 0.…”
Section: Introductionmentioning
confidence: 99%
“…Soil water in semiarid areas plays an important role in evapotranspiration [57]. The significance of evapotranspiration is confirmed as a tool for improving our understanding of environmental changes, and according to Liu et al [58], has a direct connection with society. Another important aspect is that the phytosociological approach and statistical analysis are fundamental for the study and greater knowledge of plant communities; several authors consider all these data (plus others such as phytotoponims) to be crucial to their conservation and/or restoration [20,56,[59][60][61][62][63].…”
Section: Discussionmentioning
confidence: 98%
“…The average ET of each catchment was 387.6 mm. Liu et al [45] analyzed the long-term ET data (MOD16, version 5) from 2002 to 2012, and found that the annual ET gradually declined from southwest to northeast, with the highest values in the upper Qilian Mountain area in the south (>450 mm year −1 ), followed by the middle plain area (250-400 mm year −1 ) and the lower reaches (<250 mm year −1 ). We compared the simulation ET results with MOD16/ET monthly product data (Figure 3b).…”
Section: Response Of Water Resources To Climate Warming In the Runoff...mentioning
confidence: 99%